1996
DOI: 10.1002/(sici)1099-0518(19960415)34:5<863::aid-pola15>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of poly(acrylonitrile) with amines

Abstract: SYNOPSISThe chemical modification of poly(acrylonitri1e) was carried out using monoethanolamine and lðylenediamine. The effect of the reaction conditions on the content of basic groups was studied. Polymer analogous reactions were carried out by varying the amount of the starting reagents and the temperature. The amino-containing polymers were characterized by elemental analysis. The obtained water-soluble polymers were used as carriers of low-molecular substances. 0 1996 John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Pure PS was investigated first since it was not clear if the ethylene diamine would react with the acrylonitrile. [77] An oligomer was used to get a better resolution for characterizing the end group of the polymer. It was attempted to verify this reaction by proton nuclear magnetic resonance spectroscopy ( 1 H NMR).…”
Section: Resultsmentioning
confidence: 51%
“…Pure PS was investigated first since it was not clear if the ethylene diamine would react with the acrylonitrile. [77] An oligomer was used to get a better resolution for characterizing the end group of the polymer. It was attempted to verify this reaction by proton nuclear magnetic resonance spectroscopy ( 1 H NMR).…”
Section: Resultsmentioning
confidence: 51%
“…However, the products of PAN with ethanolamine and with ethylenediamine were soluble in water depending on the amine‐nitrile group ratio. Todorov et al investigated the effect of reaction condition for obtaining maximum conversion of amino groups . They identified that the optimum condition for the reaction of nitrile group with ethylene diamine (AN: EDA, 1:5 ratio) is at 120°C for 2 hr.…”
Section: Nitrile Group Modifications In Polymersmentioning
confidence: 99%
“…An increased hydrophilicity would enhance comfort to wear since sweat could penetrate and evaporate and static cling and stain retention during laundering would be reduced (Guebitz & Cavaco-Paulo 2008). The ability of a fibre to adsorb or to covalently bind dyes has, traditionally, been improved and enhanced by physical or chemical methods (Bendak 1991;Todorov & Valkov 1996;Makhlouf et al 2007), which have recently been complemented by plasma and laser surface modification techniques (Wong et al 2000;Ferrero 2003) or UV radiation methods (Lipp-Symonowicz & Sztajnowski 2003). However, most of the classic methods are, to some extent, environmentally harmful and/or rather complex when it comes to their technological application to the fibres (Battistel et al 2001).…”
Section: Introductionmentioning
confidence: 99%